Bioacoustics reveals two new syntopic species of Adenomera Steindachner (Anura: Leptodactylidae: Leptodactylinae) in the Cerrado of central Brazil - de Carvalho, Thiago Ribeiro; Giaretta, Ariovaldo Antonio (Zootaxa, 2013)
In this paper, we describe two syntopic species of Adenomera from the Chapada dos Veadeiros microregion, northern State of Goiás, central Brazil, recognized based on morphology, color patterns, and bioacoustics. Specimens and calls were obtained in the Municipality of Teresina de Goiás, central Brazil. Adenomera cotuba sp. nov. is diagnosed from the other 16 congeneric species by its 1) small size (adult male SVL 18.6–20.5 mm) and very robust body; 2) dorsum glandular/granular with no distinctive dorsal granular rows or dorsolateral folds; 3) black or very dark dorsal coloration with no distinctive color patterns (e.g., dorsolateral or vertebral stripes); 4) toe tips not developed into flattened disks; 5) presence of antebrachial tubercle; and 6) advertisement call consisting of a well-defined series of pulsed calls (7–32 calls/series) with progressive increment in amplitude in the first third of each call series when it reaches a sustained plateau. Adenomera juikitam sp. nov. is diagnosed from the other 16 congeneric species by its 1) dorsum profusely glandular/granular with no distinctive dorsal granular rows or dorsolateral folds; 2) dorsum with a marble-like and red coloration with no distinctive color patterns (e.g., dorsolateral or vertebral stripes); 3) toe tips not developed into flattened disks; 4) small size (adult male SVL 19.1–19.5 mm) and very robust body; and 5) long (148–202 ms) advertisement call composed of 16–21pulses. Both new taxa occur in syntopy, and our data allow us to differentiate them both in temporal (pulses/call) and spectral (frequency peaks) traits of their advertisement calls. Besides, dorsal coloration is distinctive, Adenomera cotuba sp. nov. has a black or very dark-colored dorsum, whereas Adenomera juikitam sp. nov. has a marble-like and red-colored dorsum, in addition to the presence (A. cotuba sp. nov.) or absence (A. juikitam sp. nov.) of antebrachial tubercle.